Comparison of Mini‐DMEK versus predescemetal sutures as treatment of acute hydrops in keratoconus. Issue 8 (4th May 2021) - Händel, Alexander; Siebelmann, Sebastian; Hos, Deniz; Ögrünc, Ferdi; Matthaei, Mario; Cursiefen, Claus; Bachmann, Björn
Abstract: Purpose: To compare two surgical treatment options for acute corneal hydrops in keratoconus: Mini‐DMEK versus predescemetal sutures. Methods: Sixteen patients were treated by either Mini‐Descemet membrane endothelial keratoplasty (Mini‐DMEK) ( n  = 7, group 1) or predescemetal sutures ( n  = 9, group 2) early after onset of acute hydrops. Visual acuity, maximum corneal thickness (SD‐OCT) in the affected oedematous area, complications and recurrence rates were retrospectively compared between both groups. Measurements were taken immediately preoperatively as well as 1 day, 1 week and 1 month postoperatively (Table 1). Results: Both groups showed reductions in corneal thickness and increased visual acuity shortly after surgery. In group 1 (average age 33 years ± 7 years), the best corrected visual acuity (BCVA) increased from logMAR 1.65 ± 0.7 before Mini‐DMEK to logMAR 0.93 ± 0.6 30 days after Mini‐DMEK (p = 0.046). During that period, maximum corneal thickness decreased from 1159 ± 338 µm before surgery to 531 ± 75 µm after Mini‐DMEK (p = 0.046). Patients from group 2 (average age 34 ± 10 years) had a BCVA of logMAR 1.59 ± 0.8 which increased to logMAR 0.97 ± 0.5 (p = 0.014) 30 days after surgery. At the same time, the preoperative maximum corneal thickness decreased from 1439 ± 272 µm to 476 ± 162 µm (p = 0.014). There was no difference in corneal thickness or BCVA one month after the surgical intervention between both groups (p = 0.394 and p = 0.871). Conclusions: Both techniques, Mini‐DMEK and predescemetal sutures, are effective in the treatment of an acute hydrops in keratoconus. Mini‐DMEK appears to be beneficial in large DM tears.